Monocytes from HIV-infected individuals show impaired cholesterol efflux and increased foam cell formation after transendothelial migration. (31st July 2015) - Maisa, Anna; Hearps, Anna C.; Angelovich, Thomas A.; Pereira, Candida F.; Zhou, Jingling; Shi, Margaret D.Y.; Palmer, Clovis S.; Muller, William A.; Crowe, Suzanne M.; Jaworowski, Anthony
<x xml:space="preserve">Abstract</x> Design: HIV-infected (HIV+) individuals have an increased risk of atherosclerosis and cardiovascular disease which is independent of antiretroviral therapy and traditional risk factors. Monocytes play a central role in the development of atherosclerosis, and HIV-related chronic inflammation and monocyte activation may contribute to increased atherosclerosis, but the mechanisms are unknown. Methods: Using an in-vitro model of atherosclerotic plaque formation, we measured the transendothelial migration of purified monocytes from age-matched HIV+ and uninfected donors and examined their differentiation into foam cells. Cholesterol efflux and the expression of cholesterol metabolism genes were also assessed. Results: Monocytes from HIV+ individuals showed increased foam cell formation compared with controls (18.9 vs. 0%, respectively, P = 0.004) and serum from virologically suppressed HIV+ individuals potentiated foam cell formation by monocytes from both uninfected and HIV+ donors. Plasma tumour necrosis factor (TNF) levels were increased in HIV+ vs. control donors (5.9 vs. 3.5 pg/ml, P = 0.02) and foam cell formation was inhibited by blocking antibodies to TNF receptors, suggesting a direct effect on monocyte differentiation to foam cells. Monocytes from virologically suppressed HIV+ donors showed impaired cholesterol efflux and decreased expression of key genes regulating cholesterol metabolism, including the cholesterol transporter ABCA1 (P = 0.02). Conclusion: Monocytes from HIV+ individuals show impaired cholesterol efflux and are primed for foam cell formation following transendothelial migration. Factors present in HIV+ serum, including elevated TNF levels, further enhance foam cell formation. The proatherogenic phenotype of monocytes persists in virologically suppressed HIV+ individuals and may contribute mechanistically to increased atherosclerosis in this population.